Cyclic impact experimental study on the mechanical behavior of sandstone subjected to freeze-thaw cycles - Tao, Li; Peng, Wu; Shanchao, Hu; boyuan, Wu; Zhanqing, Chen (Frontiers in Earth Science, 2025)
The sandstone in open-pit coal mines frequently experiences freeze-thaw cycles and cyclic impact loads. To investigate the strength, deformation, and damage evolution laws of freeze-thaw sandstone under cyclic impacts, cyclic impact experiments was conducted by SHPB, and the failure mode was further elucidated by high-speed camera technology and SEM in the laboratory. The results indicate that: (1) The number of impacts, peak stress, and elastic modulus are negatively correlated with the number of freeze-thaw cycles. With the impacts times increasing, the peak stress and elastic modulus of sandstone initially decline gradually before plummeting sharply in the final few loadings. (2) With freeze-thaw cycles and impact quantity increasing, dissipated energy and reflected energy increase, whereas transmitted energy decreases. (3) The failure mode of sandstone is characterized by tensile failure, with cracks initially forming on the sample’s side, then propagating radially and ultimately penetrating the entire specimen. Freeze-thaw exacerbate the fragmentation of sandstone, and induce a transition from transgranular to intergranular failure. (4) As the quantity of impacts increases, the damage factor of sandstone initially rises slowly and then accelerates rapidly, which aligns with the evolution law of the peak stress of sandstone. These findings provide valuable reference for ensuring safe mining operations.